PENINGKATAN KOMPETENSI PEDAGOGIK GURU PRODUKTIF DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI IN HOUSE TRAINING (IHT) DI SD NEGERI 21 PADANG LAWEH - Zulherlita Zulherlita (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on the results of observations and supervision carried out by the author, the teacher's pedagogic competence in preparing lesson plans is still low. The purpose of this study was to describe and obtain information about improving the pedagogical competencies of productive teachers in preparing Learning Implementation Plans (RPP) through In House Training (IHT) at SD Negeri 21 Padang Laweh. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 6 productive teachers who taught at SD Negeri 21 Padang Laweh. The research data was collected using observation sheets. Data were analyzed using percentages. The results of the study indicate that the implementation of the In House Training (IHT) can improve the pedagogical competence of the teacher in preparing lesson plans. This is evidenced by the value of the initial teacher competency before the program is 74. Then after IHT activities there is an increase in the first cycle is 78.70 (good) and after that increases in the second cycle to 87.56 (Very good).